2013
DOI: 10.18052/www.scipress.com/ilns.7.1
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Ethrel on the Starch Sugar Changes of Off-Season Fruits of Mango (M<i>angifera indica</i> l. Var. Neelum) during Ripening

Abstract: The present investigation is aimed at studying the effect of ethrel on the ripening of offseason fruits of Mangifera indica L. var. Neelum. The control fruits were kept in the laboratory naturally while the experimental fruits were treated with different concentrations of ethrel (100, 200 and 300 ppm). In control fruits, partial ripening led to incomplete metabolic changes, which did not alter the presence of sourness in the fruits. Hence, they were not fit to be eaten. On the other hand, the fruits treated wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
6
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 28 publications
3
6
0
Order By: Relevance
“…Maximum decrease (0.12%) in total acidity was found in fruits treated with 1000 ppm ethrel at 11 th day of the storage treatment. Similar finding was also noted in mango Venkatesan and Tamilmani, 2013;Das et al 2011Das et al , 2013 and papaya . The result indicates that the acidity content declined significantly with the increase in days of storage.…”
Section: Effect On Total Soluble Solids (Tss)supporting
confidence: 74%
See 3 more Smart Citations
“…Maximum decrease (0.12%) in total acidity was found in fruits treated with 1000 ppm ethrel at 11 th day of the storage treatment. Similar finding was also noted in mango Venkatesan and Tamilmani, 2013;Das et al 2011Das et al , 2013 and papaya . The result indicates that the acidity content declined significantly with the increase in days of storage.…”
Section: Effect On Total Soluble Solids (Tss)supporting
confidence: 74%
“…It was reported that post-harvest treatment with ethrel promoted ripening of mango fruits, and the treated fruits were less firm than the treated ones (Mohamed Nour and Abu Goukh, 2010). A similar drop in flesh firmness was reported in guava Abu Goukh and Bashir, 2003) and mango (Venkatesan and Tamilmani, 2010). Decreasing fruit firmness might be associated with fruit softening which is coincide with the report of Ali et al (2011).…”
Section: Effect On Decaysupporting
confidence: 72%
See 2 more Smart Citations
“…The changes in physio-chemical characteristic features during ripening was studied in detail by earlier researchers (Khan et al, 2008;Rodrigo et al, 2009;Ali et al, 2011;Venkatesan and Tamilmani, 2013).…”
Section: Introductionmentioning
confidence: 99%